ANALYSIS OF THE IMPACT OF ONLINE LENDING SERVICES ON SOCIETY - NOVI PRIHATINI (Laboratorium Riset Ekonomi, 2023)
This research discusses the use of online loan services in Cirebon, Indonesia, in the context of the rapid growth of these services in the digital era. The primary focus is on analyzing financial risks, social impacts, risk perceptions and requirements, reasons for using these services, and their effects on the community. Through interviews and data analysis, this study highlights the benefits of online loan services in supporting small businesses and meeting the urgent needs of individuals. The research also emphasizes the importance of financial education and strong regulations to protect consumers and maintain the benefits of these services in the Cirebon community.